Egr‐2 transcription factor is required for Blimp‐1‐mediated IL‐10 production in IL‐27‐stimulated CD4+ T cells. Issue 4 (26th February 2013) - Iwasaki, Yukiko; Fujio, Keishi; Okamura, Tomohisa; Yanai, Atsushi; Sumitomo, Shuji; Shoda, Hirofumi; Tamura, Tomohiko; Yoshida, Hiroki; Charnay, Patrick; Yamamoto, Kazuhiko
<x xml:space="preserve">Abstract</x> Interleukin‐27 (IL‐27) suppresses immune responses through inhibition of the development of IL‐17 producing Th17 cells and induction of IL‐10 production. We previously showed that forced expression of early growth response gene 2 (Egr‐2), a transcription factor required for T‐cell anergy induction, induces IL‐10 and lymphocyte activation gene 3 expression and confers regulatory activity on CD4+ T cells in vivo. Here, we evaluated the role of Egr‐2 in IL‐27‐induced IL‐10 production. Among various IL‐10‐inducing factors, only IL‐27 induced high levels of Egr‐2 and lymphocyte activation gene 3 expression. Intriguingly, IL‐27 failed to induce IL‐10 in Egr‐2‐deficient T cells. IL‐27‐mediated induction of Prdm1 that codes B lymphocyte induced maturation protein‐1, a transcriptional regulator important for IL‐10 production in CD4+ T cells, was also impaired in the absence of Egr‐2. Although IL‐27‐mediated IL‐10 induction was dependent on both STAT1 and STAT3, only STAT3 was required for IL‐27‐mediated Egr‐2 induction. These results suggest that IL‐27 signal transduction through Egr‐2 and B lymphocyte induced maturation protein‐1 plays an important role in IL‐10 production. Furthermore, Egr‐2‐deficient CD4+ T cells showed dysregulated production of IFN‐γ and IL‐17 in response to IL‐27 stimulation. Therefore, Egr‐2 may play key roles in controlling the balance between regulatory and effector cytokines.